REFORMASI SISTEM PELAYANAN PUBLIK DI ERA DIGITAL DALAM MENJEMBATANI DAS SOLLEN DAN DAS SEIN PADA TATA KELOLA PEMERINTAHAN KOTA BUKITTINGGI - Alimah Tusak Diyah; Adria Fahyumi Alfanzha; Anisa Delia Safitri; Annisa Fadillah; Gian Yoga Nasirwan Batubara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the reform of digital public service delivery in Bukittinggi City by analyzing the gap between Das Sollen—the ideal standards of governance—and Das Sein—the actual conditions observed in implementation. The city’s digital transformation efforts demonstrate a strong commitment to enhancing efficiency, transparency, and service quality. However, findings reveal persisting challenges, including limited civil servant digital competence, fragmented system integration, and varied levels of public digital literacy. Using a descriptive qualitative approach, this research identifies how digital policies are translated into practice and evaluates the extent to which current reforms bridge the ideal and the real. The study highlights the need for capacity-building, stronger digital infrastructure, and community empowerment to achieve more inclusive and adaptive public services.